2011
DOI: 10.2147/ppa.s15702
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adherence and persistence among multiple sclerosis patients treated with disease-modifying therapies: a retrospective administrative claims analysis

Abstract: Purpose:To compare adherence and persistence among patients with multiple sclerosis (MS) initiated on disease-modifying therapy (DMTs), including intramuscular (IM) interferon beta-1a (IFNβ-1a), subcutaneous (SC) IFNβ-1a, IFNβ-1b, or glatiramer acetate (GA).Methods:MS patients initiated on IM-IFNβ-1a, SC-IFNβ-1a, IFNβ-1b, or GA between January 1, 2000 and January 2, 2008 were identified from a retrospective claims database study associated with a large US health plan. The date of DMT initiation was the index d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
4
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 30 publications
11
103
4
13
Order By: Relevance
“…Halpern et al 26 reported lower rates of adherence for GA and IFN (52.2-62.3% of patients) and Tan et al 19 reported a combined rate of 59.6%; however, both of these studies required patients to have only one claim for the index DMT (not at least two claims as in our study), and both had substantially longer follow-up periods than in our study (1-3 years and 4 years, respectively). Another 4-year study reported adherence rates of 52.2-62.3% for GA and IFNs 27 . Similar rates were also reported in a review that included 24 studies of adherence to DMTs, with weighted mean adherence rates for GA and IFNs ranging between 56.8% and 69.4% 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Halpern et al 26 reported lower rates of adherence for GA and IFN (52.2-62.3% of patients) and Tan et al 19 reported a combined rate of 59.6%; however, both of these studies required patients to have only one claim for the index DMT (not at least two claims as in our study), and both had substantially longer follow-up periods than in our study (1-3 years and 4 years, respectively). Another 4-year study reported adherence rates of 52.2-62.3% for GA and IFNs 27 . Similar rates were also reported in a review that included 24 studies of adherence to DMTs, with weighted mean adherence rates for GA and IFNs ranging between 56.8% and 69.4% 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that adherence to, and persistence with, DMTs are associated with a reduced risk of relapse 22,23 , reduced healthcare resource utilization 22 , reduced incidence of MS-related hospitalization 19 , and improved health-related quality-of-life 24,25 in patients with MS. First-line injectable DMTs are associated with sub-optimal rates of adherence and persistence 20,22,[26][27][28][29] , and treatment-related issues, such as unresponsiveness and intolerance to GA or IFNs, prompt patients to discontinue or switch therapy 30,31 . A review of DMT discontinuation rates across several countries found that 16-27% of patients discontinued GA or IFN therapy prematurely within 24 months of follow-up, increasing to 43% for GA and up to 34% for IFNs when patients were followed for longer than 24 months 32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[11][12][13][14]16 A média ponderada do desfecho MPR>0,80 dos três estudos identificados que envolveram ao todo 43.372 pacientes foi de 48,99% para Avonex®, 40,72% para Betaferon® e 43,06% para Rebif®. (11,12,14) Já a média ponderada do MPR em cinco estudos envolvendo cerca de 45 mil pacientes foi de 67,08%, 58,31% e 64,61% para Avonex®, Betaferon® e Rebif®, respectivamente.…”
Section: Discussionunclassified
“…7 Tal decisão foi baseada no Relatório de Recomendação nº 261, de maio de 2016, da Comissão Nacional [8][9][10][11][12][13][14][15][16][17][18][19] Ao identificar a dicotomia dos dois conjuntos de evidências descritos acima (i.e., monitoramento da incorporação versus literatura científica), avaliamos as principais discrepâncias entre os referidos grupos de informações e apontamos as seguintes falhas metodológicas no estudo de monitoramento da incorporação das betainterferonas no SUS, sendo:…”
Section: Antecedentesunclassified